2021
DOI: 10.1029/2020gc009326
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic Surface Displacement in the 2019 Ridgecrest Earthquakes: Comparison of Field Measurements and Optical Image Correlation Results

Abstract: A first-order problem in earthquake studies is understanding the linkage between rupture at the surface and the underlying seismogenic fault. Specifically, what do spatial patterns of surface displacement reveal about fault rupture at seismogenic depths? For a number of historical surface rupturing earthquakes, deformation has been shown to be highly localized, for example in the 1940 Imperial Valley earthquake (Rockwell & Klinger, 2013). In contrast, other surface-rupturing earthquakes have produced highly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 57 publications
4
23
0
Order By: Relevance
“…The magnitude of off‐fault deformation cannot be determined in this study due to lack of long, linear cultural markers across the surface‐rupture zone (Rockwell et al., 2002). In future work, a comparison of optical‐pixel correlation of pre‐ and post‐event satellite images with our geological measurements may provide some constraints on its magnitude (e.g., Gold et al., 2021; Milliner et al., 2015).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The magnitude of off‐fault deformation cannot be determined in this study due to lack of long, linear cultural markers across the surface‐rupture zone (Rockwell et al., 2002). In future work, a comparison of optical‐pixel correlation of pre‐ and post‐event satellite images with our geological measurements may provide some constraints on its magnitude (e.g., Gold et al., 2021; Milliner et al., 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Taking InSAR results from He et al (2022) and Jin and Fialko (2021) as examples (Figure 4), our measurements are 2.5-2.7 m (on average) lower than the InSAR-based slip maximum; the ratio between our measurements and the slip maximum is <15%. Such reduced fault displacements also have been observed in other M w 7.0+ earthquakes (e.g., the 1992 Landers, 2010 El Mayor-Cucapah, 2010 Darfield and 2019 Ridgecrest events) that occurred on low-activity strike-slip faults, and can be explained by that (a) the fault slip did not totally propagate upward to the surface (named shallow-slip deficit; e.g., Fialko et al, 2005) and/or by that (b) the fault slip was distributed across a wide deformation zone and accommodated by off-fault deformation (e.g., Dolan & Haravitch, 2014;Gold et al, 2021;Milliner et al, 2015;Rockwell et al, 2002). For the Maduo earthquake, the coseismic slip pattern from InSAR data yields low shallow-slip deficit (Chen et al, 2021;He et al, 2022;Jin & Fialko, 2021;Xu et al, 2021): for example, in Jin and Fialko (2021) and He et al (2022), the InSAR-based slip near the surface is 2.2-2.6 m (on average), accounting for 70%-90% of the slip maximum; the shallow-slip deficit is only 10%-30% (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both McGill and Rubin (1999) and Milliner et al (2015) found a weak inverse correlation between the strength of near-surface material and the amount of distributed deformation for the 1992 Landers earthquake. Zinke et al (2014) also suggested that the strength of surficial material correlates with distributed deformation for the 2013 Balochistan earthquake, and Cheng and Barnhart (2021) found no correlation between distributed deformation and inelastic strain in this rupture. Because distributed deformation is likely an integral of multiple causes, fault maturity, fault strength, and slip in prior earthquakes may also play a role.…”
Section: Variability From Distributed Deformationmentioning
confidence: 93%
“…For the studies used in this analysis, image correlation can resolve displacements of 10% or less of the image pixel size (i.e. 10 cm for 1 m-resolution images) and profile stacking is used to further smooth out noise and increase signal-tonoise ratio (Gold et al, 2015(Gold et al, , 2021Milliner et al, 2015Milliner et al, , 2016bZinke et al, 2014). Synthetic tests also demonstrate that three different correlation algorithms can resolve displacement between 1/10th and 1/100th of the image pixel size with little noise, especially when pixels with low signal-to-noise ratio are masked out (Leprince et al, 2007;Rosu et al, 2015).…”
Section: Sources Of Inherent Variabilitymentioning
confidence: 99%